Strength characteristics in saturation process and rainfall-induced landslide failure mechanism of granite residual soil - Lan, Bing; Jia, Bangzhong; Wu, Yiying; Yi, Xiaoyu; Feng, Wenkai; Li, Yihe (Frontiers in Earth Science, 2025)
The southeastern coastal areas of China have a wide distribution of granite residual soil, and the region experiences heavy rainfall, particularly during typhoons and other climatic events, leading to frequent landslides in the residual layer. This study investigates the hydro-mechanical behavior of Minqing County (Fujian Province) granite residual soils through direct shear tests and novel meso-structural analysis using scanning electron microscopy (SEM). By systematically evaluating unsaturated, saturated, and continuously saturated states, we quantify the soil’s strength deterioration mechanisms and establish, for the first time, a microstructure-based framework linking saturation-dependent structural evolution to macroscopic shear behavior. Results reveal that shear strength declines nonlinearly with increasing moisture content and saturation duration: cohesion follows a quadratic function, while the internal friction angle adheres to a logarithmic relationship. SEM imaging uncovers critical meso-scale processes, including the dissolution of clay-humic cementation and the collapse of metastable pore structures under prolonged saturation, which directly drive strength reduction. During continuous saturation, stress-strain curves exhibit strain-hardening behavior accompanied by distinct stick-slip phenomena post-shear, reflecting progressive particle rearrangement and intergranular bond degradation. Both cohesion and internal friction angle decrease asymptotically until stabilization, governed by saturation-induced microstructural homogenization. These findings provide a scientific basis for further understanding and predicting the disaster mechanisms and failure modes of granite residual soils under heavy rainfall conditions.